2015
DOI: 10.1038/labinvest.2014.132
|View full text |Cite
|
Sign up to set email alerts
|

Generation of pluripotent stem cells without the use of genetic material

Abstract: Induced pluripotent stem cells (iPSCs) provide a platform to obtain patient-specific cells for use as a cell source in regenerative medicine. Although iPSCs do not have the ethical concerns of embryonic stem cells, iPSCs have not been widely used in clinical applications, as they are generated by gene transduction. Recently, iPSCs have been generated without the use of genetic material. For example, protein-induced PSCs and chemically induced PSCs have been generated by the use of small and large (protein) mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 103 publications
0
47
0
Order By: Relevance
“…Chondrocytes can be not only isolated from cartilage, but also differentiated from somatic stem cells including mesenchymal stem cells and marrow stromal cells [2, 19, 20]. Chondrocytes have recently been generated from pluripotent stem cells like other cell types [2, 21, 22]. …”
Section: Discussionmentioning
confidence: 99%
“…Chondrocytes can be not only isolated from cartilage, but also differentiated from somatic stem cells including mesenchymal stem cells and marrow stromal cells [2, 19, 20]. Chondrocytes have recently been generated from pluripotent stem cells like other cell types [2, 21, 22]. …”
Section: Discussionmentioning
confidence: 99%
“…Typically, higher expression of MSC surface markers on hADSCs is found with increasing passage number14171819. However, we found that expression of some pluripotent genes such as Oct3/4, Nanog , and Klf4 , which were typical genes used for the transduction of somatic cells in reprogramming into hiPSCs1234, decreased after culture of cells in SVF solution on TCPS in our previous study16, whereas the pluripotent gene expression of the cells in SVF solution could be maintained after purification by filtration via porous membranes16. These surprising results indicate that hADSC characteristics depend on the method used for isolation of hADSCs from SVF solution.…”
mentioning
confidence: 75%
“…Human adipose-derived stem cells, hADSCs, can be obtained by isolation from fat tissue, which is currently a more practical source of stem cells than human induced pluripotent stem cells (hiPSCs)1234 and embryonic stem cells (hESCs)5. Currently, several clinical trials use hADSCs678, whereas only a few clinical trials have been performed using hiPSCs and hESCs910111213.…”
mentioning
confidence: 99%
“…RNAs have also been utilized to generate iPSCs while reducing the risk of genomic integration of oncogenes, and increasing reprogramming efficiency (Warren, Manos et al 2010, Anokye-Danso, Trivedi et al 2011, Subramanyam, Lamouille et al 2011, Bao, Zhu et al 2013, Rabinovich and Weissman 2013, Wang and Na 2013. In addition, protein-induced pluripotent stem cells have been reported (Kim, Kim et al 2009, Zhou, Wu et al 2009) and previously reviewed, (Higuchi, Ling et al 2015) and whole cell extracts have also been used to achieve complete reprogramming into iPSCs without the expression of transgenes (Cho, Lee et al 2010). However, these transient expression methods are extremely inefficient.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…However, these transient expression methods are extremely inefficient. The efficiency of protein-iPSC generation, for example, is approximately 0.001%, further suggesting the need for a better reprogramming method (Higuchi, Ling et al 2015).…”
Section: Chapter 1 Introductionmentioning
confidence: 99%